European Marine Biodiversity Monitoring Networks: Strengths, Weaknesses, Opportunities and Threats - Patrício, Joana; Little, Sally; Mazik, Krysia; Papadopoulou, Konstantia-Nadia; Smith, Christopher J.; Teixeira, Heliana; Hoffmann, Helene; Uyarra, Maria C.; Solaun, Oihana; Zenetos, Argyro; Kaboglu, Gokhan; Kryvenko, Olga; et al. (Frontiers in Marine Science, 2016)
By 2020, European Union Member States should achieve Good Environmental Status (GES) for eleven environmental quality descriptors for their marine waters to fulfill the Marine Strategy Framework Directive (MSFD). By the end of 2015, in coordination with the Regional Seas Conventions, each EU Member States was required to develop a marine strategy for their waters, together with other countries within the same marine region or sub-region. Coherent monitoring programs, submitted in 2014, form a key component of this strategy, which then aimed to lead to a Program of Measures (submitted in 2015). The European DEVOTES FP7 project has produced and interrogated a catalogue of EU marine monitoring related to MSFD descriptors 1 (biological diversity), 2 (non-indigenous species), 4 (food webs) and 6 (seafloor integrity). Here we detail the monitoring activity at the regional and sub-regional level for these descriptors, as well as for 11 biodiversity components, 22 habitats and the 37 anthropogenic pressures addressed. The metadata collated for existing European monitoring networks were subject to a SWOT (strengths, weaknesses, opportunities and threats) analysis. This interrogation has indicated case studies to address the following questions: a) what are the types of monitoring currently in place?; b) who does what and how?; c) is the monitoring fit-for-purpose for addressing the MSFD requirements?, and d) what are the impediments to better monitoring (e.g. costs, shared responsibilities between countries, overlaps, co-ordination)? We recommend the future means, to overcome the identified impediments and develop more robust monitoring strategies and as such the results are especially relevant to implementing coordinated monitoring networks throughout Europe, for marine policy makers, government agencies and regulatory bodies. It is emphasized that while many of the recommendations given here require better, more extensive and perhaps more costly monitoring, this is required to avoid any legal challenges to the assessments or to bodies and industries accused of causing a deterioration in marine quality. More importantly the monitoring is required to demonstrate the efficacy of management measures employed. Furthermore, given the similarity in marine management approaches in other developed systems, we consider that the recommendations are also of relevance to other regimes worldwide.